THE EFFECTIVENESS OF Acanthus Ilicifolius IN PROTECTING TIGER PRAWN (Penaeus monodon F.) FROM Vibrio harveyi INFECTION - Gina Saptiani; Slamet Budi Prayitno; Sutrisno Anggoro (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Sea holly (Achantus ilicifolius) is a mangrove plant that often used by coastal society as a traditional medicine. It is potential to be developed as the sources of pharmaceutical products. This study aims at assessing the effectiveness of sea holly leaves as antibacterial agent and as an agent to enhance the durability of shrimp against Vibrio harveyi. First, dried sea holly leaves were extracted with methanol, after that, it was fractionated with silica gel column method using solvent n-hexane, ethyl acetate, and n-butanol. The treatments given to tiger prawn were crude extract, the fraction of ethyl acetate, and n-butanol, and it was given by immersion. Next, the challenge test was conducted toward Vibrio harveyi. As the result, the extract and the leaves of A. ilicifolius possess activities of inhibiting the growth of V. harveyi in vivo, reducing the prevalence of attacks and improving survival of prawn. In general, based on clinical symptoms and pathological anatomy, n-butanol fraction of the A. ilicifolius leaves possess the best protection, along with ethyl acetate fraction and the crude.